Polymer modified asphalt cement mortar and method of making same

CN122940416APending Publication Date: 2026-10-20YICHANG YUANTONG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611030884.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

其中氯丁橡胶、丁苯橡胶对沥青的耐低温性能明显,但对沥青的耐高温性能改善效果一般;丙烯酸酯乳液、乙烯-醋酸乙烯共聚物乳液的玻璃化转变温度可调,柔韧性好,但与沥青的相容性差;环氧树脂能提高材料强度和刚度,但是材料脆性增加、柔韧性下降

Benefits of technology

(1)本申请在聚合物改性沥青水泥砂浆中添加改性纳米蒙脱土;本申请首先利用十六烷基三甲基溴化铵、KH570、双-[γ-(三乙氧基硅)丙基]四硫化物作为三元插层剂有机改性,长链季铵盐撑开蒙脱土片层间距,硅烷偶联剂接枝片层表面,同时引入S-S四硫键柔性交联位点,蒙脱土由亲水变为双亲性,可同时兼容无机水泥相、有机沥青相,实现纳米单片层均匀分散;本申请再在蒙脱土片层表面接枝MMA/BA/AA/乙烯基硅烷共聚高分子链,高分子链穿插于沥青与水泥基体,进一步强化两相界面结合,同时高分子链赋予片层微变形能力,提升基体韧性;本申请最后在蒙脱土片层外生长介孔SiO2,介孔孔道吸附游离乳化沥青微滴与水泥水化液相,填充浆体毛细孔、阻断水和腐蚀性离子渗透路径,提升抗渗、抗冻融性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention discloses polymer-modified asphalt cement mortar and its preparation method, relating to the field of cement materials technology. The method for preparing polymer-modified asphalt cement mortar includes the following steps: blending cement, fine aggregate, and modified nano-montmorillonite to obtain a dry mixture; blending a composite retarder, water-reducing agent, water, and polyacrylate / styrene-butadiene rubber core-shell emulsion to obtain a liquid phase component; blending the dry mixture, liquid phase component, and cationic emulsified asphalt, adding a defoamer, adding modified PVA fibers, and adding an air-entraining agent to obtain polymer-modified asphalt cement mortar; the polymer-modified asphalt cement mortar prepared in this application comprehensively solves the defects of traditional CA mortar, such as cracking, water loss, aging, and poor compatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of cement materials technology, specifically to polymer-modified asphalt cement mortar and its preparation method. Background Technology

[0002] Cement concrete pavement is one of the main structural forms of pavement in my country and is widely used in construction projects. However, CSH gel, the main hydration product of cement hydration, is a rigid gel. Cement paste has a high elastic modulus, and under the combined effects of freeze-thaw cycles, erosion, external loads, and internal forces, its durability decreases over time. Defects such as micropores, peeling, and erosion appear on the surface and inside, gradually evolving into cracks and broken slabs, damaging the overall stability of the pavement. Asphalt, an organic gel material, although having lower mechanical properties, has good flexibility and strong resistance to deformation, and is widely used in pavement materials. As an organic material, asphalt has a significant difference in surface tension compared to water, making it incompatible with cement-based systems. To overcome this compatibility issue, emulsified asphalt is typically used to prepare cement-emulsified asphalt composite gel systems, leading to the development of emulsified asphalt cement mortar (CA mortar). Emulsified asphalt refers to an organic emulsion formed by heating asphalt at high temperatures to create asphalt droplets, which then interact with an emulsifier in a colloid mill, resulting in a liquid that dissolves in water at room temperature. CA mortar utilizes cement hydration products to provide a rigid framework and emulsified asphalt to provide flexible deformation capabilities.

[0003] However, due to the material and mechanical properties of CA mortar, the road surface is prone to aging and has poor water resistance. Under alternating high and low temperatures and rainwater erosion, it is susceptible to deformation such as cracking, rutting, and shoving. The appearance of cracks damages the integrity of the road surface. After cracks appear, rainwater seeps into the subgrade through the cracks. Vehicle traffic generates loads on the road surface, creating wash water, which causes the mortar material to be pumped away, the subgrade to be easily eroded, and water damage to the road surface, leading to network cracking and potholes, affecting the load-bearing capacity of the structural layer, and reducing the service life of the road surface. Therefore, starting from the preparation and performance of cement emulsified asphalt mortar, polymer components are introduced to compensate for the deficiencies of CA mortar in terms of mechanical properties, crack resistance, adhesion, and durability. Material adaptability and anti-aging design and modification of the asphalt substrate are carried out to fundamentally improve the weather resistance and durability of the material. Commonly used road asphalt modifiers include chloroprene rubber, styrene-butadiene rubber, ethylene-vinyl acetate copolymer emulsion, epoxy resin emulsion, and acrylic emulsion. Chloroprene rubber and styrene-butadiene rubber significantly improve the low-temperature resistance of asphalt, but their effect on improving the high-temperature resistance of asphalt is only moderate. Acrylic ester emulsions and ethylene-vinyl acetate copolymer emulsions have adjustable glass transition temperatures and good flexibility, but poor compatibility with asphalt. Epoxy resins can improve the strength and stiffness of materials, but increase brittleness and decrease flexibility. Therefore, there is an urgent need to prepare a new type of asphalt cement mortar to solve the defects of traditional CA mortar, such as cracking, water loss, aging, and poor compatibility. Summary of the Invention

[0004] The purpose of this invention is to provide polymer-modified asphalt cement mortar and its preparation method, thereby solving the following technical problems: Existing CA mortar has defects such as low-temperature cracking, water loss, aging, and poor compatibility.

[0005] The objective of this invention can be achieved through the following technical solutions: A method for preparing polymer-modified asphalt cement mortar includes the following steps: Cement, fine aggregate, and modified nano-montmorillonite are blended to obtain a dry mix; The composite retarder, water-reducing agent, water, and polyacrylate / styrene-butadiene rubber core-shell emulsion were blended to obtain the liquid phase component; The dry mixture, liquid phase component, and cationic emulsified asphalt are blended together, and a defoamer is added for blending. Modified PVA fiber is added for blending, and an air-entraining agent is added for blending to obtain polymer-modified asphalt cement mortar. Modified nano-montmorillonite is obtained by organic treatment with hexadecyltrimethylammonium bromide, KH570, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide as intercalating agents, followed by polymer interface modification and surface mesoporous silica functionalization. The preparation method of modified PVA fibers includes the following steps: A1: Anhydrous ethanol, deionized water, and 25-28 wt% ammonia water are added to a reaction flask and dispersed. The temperature is controlled at 30-35℃. Plasma-activated PVA fibers are added, and tetraethyl orthosilicate is added. The temperature is controlled at 30-40℃ and the reaction is stirred for 6-12 hours. The mixture is then filtered, washed, and dried to obtain silica-modified PVA fibers. A2: Cetyltrimethylammonium bromide, deionized water, and anhydrous ethanol were added to a reaction flask for dispersion. 25-28 wt% ammonia water was added for dispersion. Silica-modified PVA fibers were added, along with tetraethyl orthosilicate. The reaction was carried out at a temperature of 40-50℃ with stirring for 12-24 hours. The mixture was filtered, and the solid was immersed in an ethanol mixture containing hydrochloric acid. The mixture was refluxed for 6-12 hours for extraction. After washing and drying, mesoporous silica-modified PVA fibers were obtained. A3: Sodium alginate, deionized water, and lithium silicate are mixed together, and mesoporous silica-modified PVA fibers are added. The temperature is controlled at 40-50℃ and kept warm for 0.5-1h. After filtration, the solid is immersed in calcium chloride solution and the temperature is controlled at 20-25℃ for 10-30min. After washing and drying, modified PVA fibers are obtained.

[0006] As a further aspect of the present invention, the preparation method of plasma-activated PVA fibers includes the following steps: washing PVA fibers with acetone, washing with deionized water, drying, and treating them in an oxygen atmosphere at 50-100W for 3-5 minutes.

[0007] As a further embodiment of the present invention: the addition ratio of anhydrous ethanol, deionized water, 25-28wt% ammonia, plasma-activated PVA fiber, and tetraethyl orthosilicate in A1 is 150-200mL: 20-40mL: 2-4mL: 10g: 3-6mL; A2 contains ethanol and hydrochloric acid mixtures composed of 100-150 mL of anhydrous ethanol and 1-2 mL of 37 wt% hydrochloric acid aqueous solution; The addition ratio of hexadecyltrimethylammonium bromide, deionized water, anhydrous ethanol, 25-28 wt% ammonia, silica-modified PVA fiber, tetraethyl orthosilicate, and ethanol containing hydrochloric acid in A2 is 0.5-1.5 g: 50-80 mL: 100-150 mL: 1-3 mL: 10 g: 2-5 mL: 100-150 mL; The calcium chloride solution in A3 is a 0.5-1 wt% aqueous solution of calcium chloride; The addition ratio of sodium alginate, deionized water, lithium silicate, mesoporous silica-modified PVA fiber, and calcium chloride solution in A3 is 1-2g: 50-100mL: 0.1-0.3g: 10g: 50-100mL.

[0008] As a further aspect of the present invention, the preparation method of modified nano-montmorillonite includes the following steps: B1: Sodium-based montmorillonite and deionized water were added to a reaction vessel and ultrasonically treated. The temperature was controlled at 45-55℃. Hexadecyltrimethylammonium bromide, KH570, bis-[γ-(triethoxysilyl)propyl]tetrasulfide and anhydrous ethanol were mixed and added to the reaction vessel. Hydrochloric acid was added to adjust the pH to 4-5. The temperature was controlled at 55-65℃ and the reaction was kept at this temperature for 3-6 hours. The mixture was washed and dried to obtain organically modified montmorillonite. B2: Under a nitrogen atmosphere, organic modified montmorillonite, anhydrous ethanol, and azobisisobutyronitrile were added to a reaction flask and mixed. Methyl methacrylate, butyl acrylate, acrylic acid, and vinyltriethoxysilane were added. The temperature was controlled at 60-70℃ and the reaction was kept at this temperature for 6-9 hours. After centrifugation, washing, and drying, polymer-modified montmorillonite was obtained. B3: Polymer-modified montmorillonite, hexadecyltrimethylammonium bromide, anhydrous ethanol, and deionized water were added to a reaction vessel and mixed. Ammonia was added to adjust the pH to 10-11. Tetraethyl orthosilicate was added, and the temperature was controlled at 40-50℃ for 6-12 hours. KH550 was added, and the reaction was maintained for 3-6 hours. After centrifugation and washing, the mixture was added to an ethanol mixture containing hydrochloric acid and refluxed for 4-6 hours. After washing and drying, modified nano-montmorillonite was obtained.

[0009] As a further embodiment of the present invention, the preparation method of sodium-based montmorillonite includes the following steps: adding montmorillonite and deionized water into a reaction flask for mixing, controlling the temperature at 50-60℃ and keeping the reaction at this temperature for 1-2 hours, adding sodium carbonate, keeping the reaction at this temperature and stirring for 3-6 hours, centrifuging, washing and drying to obtain sodium-based montmorillonite. The addition ratio of montmorillonite, deionized water, and sodium carbonate is 10g: 100-200mL: 0.5-1g.

[0010] As a further embodiment of the present invention: the addition ratio of sodium montmorillonite, deionized water, hexadecyltrimethylammonium bromide, KH570, bis-[γ-(triethoxysilyl)propyl]tetrasulfide, and anhydrous ethanol in B1 is 10g: 100-200mL: 1.5-2.5g: 0.5-1g: 0.4-0.8g: 20-40mL; The addition ratio of organic modified montmorillonite, anhydrous ethanol, azobisisobutyronitrile, methyl methacrylate, butyl acrylate, acrylic acid, and vinyltriethoxysilane in B2 is 10g: 100-200mL: 0.2-0.4g: 7-10g: 4-6g: 1-3g: 0.8-1.2g; B3 contains an ethanol mixture with hydrochloric acid, which consists of 100-150 mL of anhydrous ethanol and 1-2 mL of 37 wt% hydrochloric acid aqueous solution. The addition ratio of polymer-modified montmorillonite, hexadecyltrimethylammonium bromide, anhydrous ethanol, deionized water, tetraethyl orthosilicate, and KH550 in B3 is 10g: 1.5-2.5g: 80-160mL: 20-40mL: 4-6mL: 0.8-1.2g.

[0011] As a further aspect of the present invention, the preparation method of the polyacrylate / styrene-butadiene rubber core-shell emulsion includes the following steps: C1: Butadiene, styrene, and methacrylic acid are added to a reaction flask and mixed together. Allyloxynonylphenol polyoxyethylene ether ammonium sulfate, sodium dodecylbenzene sulfonate, OP-10, and deionized water are added and mixed together to obtain a core layer pre-emulsion. Methyl methacrylate, butyl acrylate, glycidyl methacrylate, N-hydroxymethylacrylamide, and acrylic acid were added to a reaction flask and dispersed. Allyloxynonylphenol polyoxyethylene ether ammonium sulfate and deionized water were added and mixed to obtain a shell pre-emulsion. Potassium persulfate and deionized water were mixed to obtain a core layer initiator solution; Potassium persulfate and deionized water were mixed to obtain a core layer initiator solution; C2: Add sodium bicarbonate and deionized water to the reaction flask and mix. Control the temperature at 50-55℃. Add part of the core layer pre-emulsion and part of the core layer initiator solution. Keep the reaction at this temperature until the system emits a bluish light. Add the remaining core layer pre-emulsion and the remaining core layer initiator solution. Continue to keep the reaction at this temperature for 2-3 hours. Raise the temperature to 75-80℃, add the shell layer pre-emulsion and the shell layer initiator solution. Keep the reaction at this temperature for 3-6 hours. Control the temperature at 30-40℃. Add ammonia water to adjust the pH to 7.5-8. Sieve the mixture to obtain a polyacrylate / styrene-butadiene rubber core-shell emulsion.

[0012] As a further aspect of the present invention: the core layer preemulsion comprises the following raw materials in parts by weight: 45-60 parts by weight of butadiene, 25-35 parts by weight of styrene, 2-5 parts by weight of methacrylic acid, 1.2-2.4 parts by weight of allyloxynonylphenol polyoxyethylene ether ammonium sulfate, 0.5-1.5 parts by weight of sodium dodecylbenzenesulfonate, 0.5-1.5 parts by weight of OP-10, and 40-60 parts by weight of deionized water; The shell preemulsion comprises the following raw materials in parts by weight: 25-35 parts by weight of methyl methacrylate, 15-20 parts by weight of butyl acrylate, 8-12 parts by weight of glycidyl methacrylate, 3-6 parts by weight of N-hydroxymethylacrylamide, 2-5 parts by weight of acrylic acid, 0.8-1.6 parts by weight of allyloxynonylphenol polyoxyethylene ether ammonium sulfate, and 30-45 parts by weight of deionized water; The core layer initiator solution comprises the following raw materials in parts by weight: 0.2-0.4 parts by weight of potassium persulfate and 7.5-11.25 parts by weight of deionized water; The shell initiator solution comprises the following raw materials in parts by weight: 0.2-0.4 parts by weight of potassium persulfate and 7.5-11.25 parts by weight of deionized water; The mass ratio of partial core layer preemulsion to remaining core layer preemulsion is 1:4; The mass ratio of a portion of the core layer initiator solution to the remaining core layer initiator is 1:3; The mass ratio of sodium bicarbonate, deionized water, and shell initiator solution in C2 is 0.2-0.5: 15-22.5: 7.7-11.65.

[0013] As a further aspect of the present invention: the polymer-modified asphalt cement mortar comprises the following raw materials in parts by weight: 100 parts by weight of cement, 150-200 parts by weight of fine aggregate, 0.5-2 parts by weight of modified nano-montmorillonite, 0.2-0.5 parts by weight of composite retarder, 0.5-1 parts by weight of water-reducing agent, 10-20 parts by weight of polyacrylate / styrene-butadiene rubber core-shell emulsion, 30-50 parts by weight of cationic emulsified asphalt blend, and 0.1-0.3 parts by weight of defoamer, 0.5-1.5 parts by weight of modified PVA fiber, and 0.01-0.05 parts by weight of air-entraining agent; the water-cement ratio of the polymer-modified asphalt cement mortar is 0.38-0.45.

[0014] As a further aspect of the present invention: the cement is silicate cement; The fine aggregate is river sand with a particle size of 0.16-4.75 mm and a fineness modulus of 1.8-2.6; The composite retarder is composed of citric acid and aluminum sulfate in a mass ratio of 1:1; The water-reducing agent is a polycarboxylate water-reducing agent; The defoamer is an organosilicone defoamer; The air-entraining agent is a rosin-based air-entraining agent.

[0015] Polymer-modified asphalt cement mortar is prepared by any of the above preparation methods.

[0016] PVA fiber is a type of PVA fiber with a length of 6-12 mm, a diameter of 15-30 μm, and a tensile strength ≥1.2 GPa.

[0017] The beneficial effects of this invention are: (1) This application adds modified nano-montmorillonite to polymer-modified asphalt cement mortar; this application first uses hexadecyltrimethylammonium bromide, KH570, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide as ternary intercalating agents for organic modification, long-chain quaternary ammonium salts to expand the interlayer spacing of montmorillonite, silane coupling agents to graft the surface of the interlayers, and at the same time introduces SS tetrasulfide flexible crosslinking sites, so that montmorillonite changes from hydrophilic to amphiphilic, and can be compatible with both inorganic cement phase and organic asphalt phase, so as to achieve uniform nano-monolayers. Dispersion; In this application, MMA / BA / AA / vinylsilane copolymer polymer chains are grafted onto the surface of the montmorillonite sheets. The polymer chains interpenetrate in the asphalt and cement matrix, further strengthening the interfacial bonding between the two phases. At the same time, the polymer chains endow the sheets with micro-deformation ability and improve the toughness of the matrix. Finally, mesoporous SiO2 is grown on the outside of the montmorillonite sheets. The mesoporous channels adsorb free emulsified asphalt droplets and cement hydration liquid phase, fill the capillary pores of the slurry, block the penetration paths of water and corrosive ions, and improve the impermeability and freeze-thaw resistance.

[0018] (2) This application adds a polyacrylate / styrene-butadiene rubber core-shell emulsion to polymer-modified asphalt cement mortar. The core layer of the polyacrylate / styrene-butadiene rubber core-shell emulsion is a butadiene-styrene rubber phase. Flexible rubber segments are embedded in the rigid skeleton of cement hydration CSH, which acts as a flexible buffer phase to absorb internal stress generated by temperature change and load. At low temperature, it relaxes stress and inhibits cracking, and at high temperature, it improves creep resistance and rutting resistance. The shell layer is composed of glycidyl methacrylate and N-hydroxymethylacrylamide modified acrylate. The shell layer contains epoxy groups, hydroxymethyl groups and carboxyl groups. The carboxyl groups can react chemically with cement hydration Ca(OH)2. The epoxy groups are chemically bonded to cement hydration hydroxyl groups and asphalt active groups, bridging the inorganic phase of cement and the organic phase of asphalt at the molecular level, solving the problem of incompatibility and separation between conventional asphalt emulsion and cement, and strengthening the interfacial bonding between the two phases.

[0019] (3) In this application, modified PVA fibers are added to polymer-modified asphalt cement mortar. First, tetraethyl orthosilicate is used to coat SiO2 on PVA fibers to introduce silanol groups. The silanol groups are bonded to CSH and Ca(OH)2 silanol products of cement hydration, which initially improves the chemical anchoring force between the fibers and the mortar matrix. Then, tetraethyl orthosilicate is used to form porous mesoporous SiO2 on the fiber surface. The cement hydration paste can be embedded in the mesoporous channels to form a mechanically interlocked anchoring structure, which greatly improves the interfacial bonding force. The fibers are not easy to pull out when under stress, and the micro-cracks are effectively bridged. Finally, sodium alginate, lithium silicate, and calcium chloride are used to generate calcium alginate gel layer in situ on the fiber surface. The gel layer can deform appropriately with cement hydration, buffer the modulus difference between the fibers and the rigid matrix, and avoid interface debonding and cracking under temperature change. Lithium silicate slowly dissolves and reacts with cement hydration Ca(OH)2 to generate hydrated calcium silicate, which is reinforced in situ around the fibers and further densifies the interfacial area around the fibers.

[0020] (4) This application also adds a composite retarder, polycarboxylate superplasticizer, organosilicon defoamer and rosin air-entraining agent to the polymer modified asphalt cement mortar. This application adds citric acid and aluminum sulfate as composite retarder to synergistically regulate the cement hydration rate and prevent cement from setting too quickly and encapsulating asphalt particles; polycarboxylate superplasticizer disperses cement particles and modified filler, reduces mixing water consumption and reduces drying shrinkage pores; defoaming eliminates large air bubbles introduced by the emulsion, and air-entraining agent introduces uniform micropores. Micropores buffer freeze-thaw expansion stress and improve freeze-thaw resistance and durability.

[0021] This application utilizes polyacrylate / styrene-butadiene rubber core-shell emulsion to regulate the two-phase interface and enhance flexibility and toughness; utilizes modified PVA fibers to achieve macroscopic and microscopic multi-level crack resistance; and utilizes modified montmorillonite to create dense nanoscale pores and seal seepage channels. These three elements synergistically construct a dense and continuous composite network at three scales: nanofiller, polymer continuous phase, and fiber toughening, comprehensively solving the defects of traditional CA mortar such as cracking, water loss, aging, and poor compatibility. Detailed Implementation

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] Example 1: A method for preparing a polyacrylate / styrene-butadiene rubber core-shell emulsion, comprising the following steps: A1: Add 45g butadiene, 25g styrene, and 2g methacrylic acid to a reaction flask and mix. Then add 1.2g allyloxynonylphenol polyoxyethylene ether ammonium sulfate, 0.5g sodium dodecylbenzenesulfonate, 0.5g OP-10, and 40g deionized water and mix to obtain a core layer pre-emulsion. 25g of methyl methacrylate, 15g of butyl acrylate, 8g of glycidyl methacrylate, 3g of N-hydroxymethylacrylamide, and 2g of acrylic acid were added to a reaction flask and dispersed. Then, 0.8g of allyloxynonylphenol polyoxyethylene ether ammonium sulfate and 30g of deionized water were added and mixed to obtain a shell pre-emulsion. 0.3g of potassium persulfate and 10g of deionized water were mixed to obtain a core layer initiator solution; 0.3g of potassium persulfate and 10g of deionized water were mixed to obtain a core layer initiator solution; A2: Add 0.2g sodium bicarbonate and 15g deionized water to a reaction flask and mix. Control the temperature at 50℃, add 20% of the core layer pre-emulsion and 25% of the core layer initiator solution, and keep the reaction at this temperature until the system emits a bluish light. Add the remaining core layer pre-emulsion and the remaining core layer initiator solution, and continue to keep the reaction at this temperature for 2 hours. Raise the temperature to 75℃, add the shell layer pre-emulsion and the shell layer initiator solution, and keep the reaction at this temperature for 3 hours. Control the temperature at 30℃, add ammonia water to adjust the pH to 7.5, and pass the mixture through a 200-mesh sieve to obtain a polyacrylate / styrene-butadiene rubber core-shell emulsion.

[0024] The preparation method of modified PVA fibers includes the following steps: B1: PVA fibers (8mm in length, 21μm in diameter, and 1.35GPa tensile strength) were cleaned with acetone, deionized water, and dried. They were then treated in an oxygen atmosphere at 100W for 5 minutes to obtain plasma-activated PVA fibers. 150 mL of anhydrous ethanol, 20 mL of deionized water, and 2 mL of 28 wt% ammonia were added to a reaction flask and dispersed. The temperature was controlled at 30 °C. 10 g of plasma-activated PVA fiber was added, along with 3 mL of tetraethyl orthosilicate. The reaction was carried out at 30 °C and stirred for 6 h. The mixture was then filtered, washed, and dried to obtain silica-modified PVA fiber. B2: 0.5g hexadecyltrimethylammonium bromide, 50mL deionized water, and 100mL anhydrous ethanol were added to a reaction flask for dispersion. 1mL of 28wt% ammonia water was added for dispersion, 10g of silica-modified PVA fiber was added, and 2mL of tetraethyl orthosilicate was added. The reaction was carried out at 40℃ with stirring for 12h. The filtered solid was mixed with 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution to obtain a mixture. The solid was immersed in the mixture and refluxed for 6h. After washing and drying, mesoporous silica-modified PVA fiber was obtained. B3: Mix 1g sodium alginate, 50mL deionized water, and 0.1g lithium silicate, add 10g mesoporous silica-modified PVA fiber, control the temperature at 40℃ and keep it warm for 0.5h, filter, take the solid and immerse it in 50mL 1wt% calcium chloride solution, control the temperature at 20℃ and treat for 10min, wash and dry to obtain modified PVA fiber.

[0025] The preparation method of modified nano-montmorillonite includes the following steps: C1: Add 10g of montmorillonite and 100mL of deionized water to a reaction flask and mix. Control the temperature at 50℃ and keep the reaction at this temperature for 1h. Add 0.5g of sodium carbonate, keep the reaction at this temperature and stir for 3h. Centrifuge, wash and dry to obtain sodium-based montmorillonite. C2: Add 10g of sodium montmorillonite and 100mL of deionized water to a reaction vessel, and ultrasonically exfoliate at 400W for 1h while controlling the temperature at 45℃. Add 1.5g of hexadecyltrimethylammonium bromide, 0.5g of KH570, 0.4g of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, and 20mL of anhydrous ethanol to the reaction vessel. Adjust the pH to 4 with hydrochloric acid, control the temperature at 55℃, and keep the reaction at this temperature for 3h. Wash and dry to obtain organically modified montmorillonite. C3: Under a nitrogen atmosphere, 10g of organically modified montmorillonite, 100mL of anhydrous ethanol, and 0.2g of azobisisobutyronitrile were added to a reaction flask and mixed. Then, 7g of methyl methacrylate, 4g of butyl acrylate, 1g of acrylic acid, and 0.8g of vinyltriethoxysilane were added. The temperature was controlled at 60℃ and the reaction was maintained for 6h. After centrifugation, washing, and drying, polymer-modified montmorillonite was obtained. C4: 10g of polymer-modified montmorillonite, 1.5g of cetyltrimethylammonium bromide, 80mL of anhydrous ethanol, and 20mL of deionized water were added to a reaction vessel and mixed. Ammonia was added to adjust the pH to 10. 4mL of tetraethyl orthosilicate was added, and the temperature was controlled at 40℃ for 6h. 0.8g of KH550 was added, and the reaction was maintained for 3h. The solid was obtained by centrifugation and washing. 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution were mixed to prepare a solution. The solid was immersed in the mixture and refluxed for 6h. After washing and drying, modified nano-montmorillonite was obtained.

[0026] A method for preparing polymer-modified asphalt cement mortar includes the following steps: S1: Mix 100 parts by weight of silicate cement (P.I 42.5 silicate cement purchased from Qufu Zhonglian Cement), 150 parts by weight of fine aggregate (particle size 0.16-4.75mm, fineness modulus 2.56), and 2 parts by weight of modified nano-montmorillonite at 80 rpm for 90 s to obtain a dry mix. 0.2 parts by weight of citric acid, 0.2 parts by weight of aluminum sulfate, 0.8 parts by weight of polycarboxylate superplasticizer (PCA polycarboxylate superplasticizer purchased from Jiangsu Subote New Materials), water, and 20 parts by weight of polyacrylate / styrene-butadiene rubber core-shell emulsion were mixed at 150 rpm for 60 s to obtain the liquid phase component. S2: Mix the dry mixture, liquid phase component, and 30-50 parts by weight of cationic emulsified asphalt (purchased from Anhui Zhongtie Engineering Materials Technology Co., Ltd., asphalt solid content 58.5%) at 180 rpm for 60 s, add 0.2 parts by weight of organosilicon defoamer (GX-15H organosilicon defoamer from Nanjing Xunxiao Environmental Protection Technology Co., Ltd.), mix at 300 rpm for 60 s, add 1.5 parts by weight of modified PVA fiber, mix at 150 rpm for 40 s, add 0.03 parts by weight of sodium rosinate, and mix at 120 rpm for 30 s to obtain polymer-modified asphalt cement mortar with a water-cement ratio of 0.4.

[0027] Example 2: A method for preparing a polyacrylate / styrene-butadiene rubber core-shell emulsion, comprising the following steps: A1: Add 55g butadiene, 30g styrene, and 3.5g methacrylic acid to a reaction flask and mix. Then add 1.8g allyloxynonylphenol polyoxyethylene ether ammonium sulfate, 1g sodium dodecylbenzenesulfonate, 1g OP-10, and 50g deionized water and mix to obtain a core layer pre-emulsion. 30g of methyl methacrylate, 17g of butyl acrylate, 10g of glycidyl methacrylate, 4.5g of N-hydroxymethylacrylamide, and 3.5g of acrylic acid were added to a reaction flask and dispersed. Then, 1.2g of allyloxynonylphenol polyoxyethylene ether ammonium sulfate and 40g of deionized water were added and mixed to obtain a shell preemulsion. 0.3g of potassium persulfate and 10g of deionized water were mixed to obtain a core layer initiator solution; 0.3g of potassium persulfate and 10g of deionized water were mixed to obtain a core layer initiator solution; A2: Add 0.3g sodium bicarbonate and 20g deionized water to a reaction flask and mix. Control the temperature at 50℃, add 20% of the core layer pre-emulsion and 25% of the core layer initiator solution, and keep the reaction at this temperature until the system emits a bluish light. Add the remaining core layer pre-emulsion and the remaining core layer initiator solution, and continue to keep the reaction at this temperature for 2.5h. Raise the temperature to 80℃, add the shell layer pre-emulsion and the shell layer initiator solution, and keep the reaction at this temperature for 4.5h. Control the temperature at 35℃, add ammonia water to adjust the pH to 8, and pass the mixture through a 200-mesh sieve to obtain a polyacrylate / styrene-butadiene rubber core-shell emulsion.

[0028] The preparation method of modified PVA fibers includes the following steps: B1: PVA fibers (8mm in length, 21μm in diameter, and 1.35GPa tensile strength) were cleaned with acetone, deionized water, and dried. They were then treated in an oxygen atmosphere at 100W for 5 minutes to obtain plasma-activated PVA fibers. 150 mL of anhydrous ethanol, 30 mL of deionized water, and 3 mL of 28 wt% ammonia were added to a reaction flask and dispersed. The temperature was controlled at 30 °C. 10 g of plasma-activated PVA fiber was added, along with 3-6 mL of tetraethyl orthosilicate. The temperature was controlled at 30-40 °C, and the mixture was stirred for 6-12 h. The mixture was then filtered, washed, and dried to obtain silica-modified PVA fiber. B2: 1g hexadecyltrimethylammonium bromide, 50mL deionized water, and 150mL anhydrous ethanol were added to a reaction flask for dispersion. 2mL of 28wt% ammonia water was added for dispersion, followed by 10g of silica-modified PVA fiber and 3.5mL of tetraethyl orthosilicate. The reaction was carried out at 45℃ with stirring for 18h. The filtered solid was mixed with 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution to obtain a mixture. The solid was immersed in the mixture and refluxed for 8h. After washing and drying, mesoporous silica-modified PVA fiber was obtained. B3: Mix 1.5g sodium alginate, 100mL deionized water, and 0.2g lithium silicate, add 10g mesoporous silica-modified PVA fiber, control the temperature at 45℃ and keep it warm for 0.5h, filter, take the solid and immerse it in 50mL 1wt% calcium chloride solution, control the temperature at 25℃ and treat for 20min, wash and dry to obtain modified PVA fiber.

[0029] The preparation method of modified nano-montmorillonite includes the following steps: C1: Add 10g of montmorillonite and 150mL of deionized water to a reaction flask and mix. Control the temperature at 55℃ and keep the reaction at this temperature for 1.5h. Add 0.7g of sodium carbonate, keep the reaction at this temperature and stir for 4.5h. Centrifuge, wash and dry to obtain sodium-based montmorillonite. C2: Add 10g of sodium montmorillonite and 150mL of deionized water to a reaction vessel, and ultrasonically exfoliate at 400W for 1h while controlling the temperature at 50℃. Add 2g of hexadecyltrimethylammonium bromide, 0.7g of KH570, 0.6g of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, and 30mL of anhydrous ethanol to the reaction vessel. Adjust the pH to 5 with hydrochloric acid, control the temperature at 60℃, and keep the reaction at this temperature for 4.5h. Wash and dry to obtain organically modified montmorillonite. C3: Under a nitrogen atmosphere, 10g of organically modified montmorillonite, 150mL of anhydrous ethanol, and 0.3g of azobisisobutyronitrile were added to a reaction flask and mixed. Then, 8.5g of methyl methacrylate, 5g of butyl acrylate, 2g of acrylic acid, and 1g of vinyltriethoxysilane were added. The temperature was controlled at 65℃ and the reaction was maintained for 7.5h. After centrifugation, washing, and drying, polymer-modified montmorillonite was obtained. C4: 10g of polymer-modified montmorillonite, 2g of hexadecyltrimethylammonium bromide, 120mL of anhydrous ethanol, and 30mL of deionized water were added to a reaction vessel and mixed. Ammonia was added to adjust the pH to 11. 5mL of tetraethyl orthosilicate was added, and the temperature was controlled at 45℃ for 9h. 1g of KH550 was added, and the reaction was maintained for 4.5h. The solid was obtained by centrifugation and washing. 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution were mixed to prepare a solution. The solid was immersed in the mixture and refluxed for 6h. After washing and drying, modified nano-montmorillonite was obtained.

[0030] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the polyacrylate / styrene-butadiene rubber core-shell emulsion, modified PVA fiber, and modified nano-montmorillonite added in Example 1 are replaced with the polyacrylate / styrene-butadiene rubber core-shell emulsion, modified PVA fiber, and modified nano-montmorillonite prepared in Example 2. The other components and preparation methods are completely the same as those of Example 1.

[0031] Example 3: A method for preparing a polyacrylate / styrene-butadiene rubber core-shell emulsion, comprising the following steps: A1: Add 60g butadiene, 35g styrene, and 5g methacrylic acid to a reaction flask and mix. Then add 2.4g allyloxynonylphenol polyoxyethylene ether ammonium sulfate, 1.5g sodium dodecylbenzenesulfonate, 1.5g OP-10, and 60g deionized water and mix to obtain a core layer pre-emulsion. 35g of methyl methacrylate, 20g of butyl acrylate, 12g of glycidyl methacrylate, 6g of N-hydroxymethylacrylamide, and 5g of acrylic acid were added to a reaction flask and dispersed. Then, 1.6g of allyloxynonylphenol polyoxyethylene ether ammonium sulfate and 45g of deionized water were added and mixed to obtain a shell pre-emulsion. 0.3g of potassium persulfate and 10g of deionized water were mixed to obtain a core layer initiator solution; 0.3g of potassium persulfate and 10g of deionized water were mixed to obtain a core layer initiator solution; A2: Add 0.5g sodium bicarbonate and 20g deionized water to the reaction flask and mix. Control the temperature at 55℃. Add 20% core layer preemulsion and 25% core layer initiator solution. Keep the reaction at this temperature until the system emits a bluish glow. Add the remaining core layer preemulsion and the remaining core layer initiator solution. Continue to keep the reaction at this temperature for 3 hours. Raise the temperature to 80℃, add the shell layer preemulsion and the shell initiator solution. Keep the reaction at this temperature for 6 hours. Control the temperature at 40℃, add ammonia water to adjust the pH to 8, and pass the mixture through a 200-mesh sieve to obtain a polyacrylate / styrene-butadiene rubber core-shell emulsion.

[0032] The preparation method of modified PVA fibers includes the following steps: B1: PVA fibers (8mm in length, 21μm in diameter, and 1.35GPa tensile strength) were cleaned with acetone, deionized water, and dried. They were then treated in an oxygen atmosphere at 100W for 5 minutes to obtain plasma-activated PVA fibers. 200 mL of anhydrous ethanol, 40 mL of deionized water, and 4 mL of 28 wt% ammonia were added to a reaction flask and dispersed. The temperature was controlled at 35 °C. 10 g of plasma-activated PVA fiber was added, along with 6 mL of tetraethyl orthosilicate. The temperature was controlled at 40 °C, and the mixture was stirred for 12 h. The mixture was then filtered, washed, and dried to obtain silica-modified PVA fiber. B2: 1.5g of hexadecyltrimethylammonium bromide, 80mL of deionized water, and 150mL of anhydrous ethanol were added to a reaction flask for dispersion. 3mL of 28wt% ammonia water was added for dispersion, 10g of silica-modified PVA fiber was added, and 5mL of tetraethyl orthosilicate was added. The reaction was carried out at 50℃ with stirring for 24h. The filtered solid was mixed with 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution to obtain a mixture. The solid was immersed in the mixture and refluxed for 12h. After washing and drying, mesoporous silica-modified PVA fiber was obtained. B3: Mix 2g sodium alginate, 100mL deionized water, and 0.3g lithium silicate, add 10g mesoporous silica-modified PVA fiber, control the temperature at 50℃ and keep it warm for 1h, filter, take the solid and immerse it in 100mL 1wt% calcium chloride solution, control the temperature at 25℃ and treat for 30min, wash and dry to obtain modified PVA fiber.

[0033] The preparation method of modified nano-montmorillonite includes the following steps: C1: Add 10g of montmorillonite and 200mL of deionized water to a reaction flask and mix. Control the temperature at 60℃ and keep the reaction at this temperature for 2 hours. Add 1g of sodium carbonate, keep the temperature and stir for 6 hours, centrifuge, wash and dry to obtain sodium-based montmorillonite. C2: Add 10g of sodium montmorillonite and 200mL of deionized water to a reaction vessel, and ultrasonically exfoliate at 400W for 1h while controlling the temperature at 55℃. Add 2.5g of cetyltrimethylammonium bromide, 1g of KH570, 0.8g of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, and 40mL of anhydrous ethanol to the reaction vessel. Adjust the pH to 5 with hydrochloric acid, control the temperature at 65℃, and keep the reaction at this temperature for 6h. Wash and dry to obtain organically modified montmorillonite. C3: Under a nitrogen atmosphere, 10g of organically modified montmorillonite, 200mL of anhydrous ethanol, and 0.4g of azobisisobutyronitrile were added to a reaction flask and mixed. Then, 10g of methyl methacrylate, 6g of butyl acrylate, 3g of acrylic acid, and 1.2g of vinyltriethoxysilane were added. The temperature was controlled at 70℃ and the reaction was maintained for 9h. After centrifugation, washing, and drying, polymer-modified montmorillonite was obtained. C4: 10g of polymer-modified montmorillonite, 2.5g of cetyltrimethylammonium bromide, 160mL of anhydrous ethanol, and 40mL of deionized water were added to a reaction vessel and mixed. Ammonia was added to adjust the pH to 11. 6mL of tetraethyl orthosilicate was added, and the temperature was controlled at 50℃ for 12h. 1.2g of KH550 was added, and the reaction was maintained for 6h. The solid was obtained by centrifugation and washing. 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution were mixed to prepare a solution. The solid was immersed in the mixture and refluxed for 6h. After washing and drying, modified nano-montmorillonite was obtained.

[0034] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the polyacrylate / styrene-butadiene rubber core-shell emulsion, modified PVA fiber, and modified nano-montmorillonite added in Example 1 are replaced with the polyacrylate / styrene-butadiene rubber core-shell emulsion, modified PVA fiber, and modified nano-montmorillonite prepared in Example 3. The other components and preparation methods are completely the same as those of Example 1.

[0035] Comparative Example 1: A method for preparing a polyacrylate / styrene-butadiene rubber core-shell emulsion, comprising the following steps: A1: Add 55g butadiene, 30g styrene, and 3.5g methacrylic acid to a reaction flask and mix. Then add 1.8g allyloxynonylphenol polyoxyethylene ether ammonium sulfate, 1g sodium dodecylbenzenesulfonate, 1g OP-10, and 50g deionized water and mix to obtain a core layer pre-emulsion. 30g of methyl methacrylate, 17g of butyl acrylate and 3.5g of acrylic acid were added to a reaction flask and dispersed. Then, 1.2g of allyloxynonylphenol polyoxyethylene ether ammonium sulfate and 40g of deionized water were added and mixed to obtain a shell pre-emulsion. 0.3g of potassium persulfate and 10g of deionized water were mixed to obtain a core layer initiator solution; 0.3g of potassium persulfate and 10g of deionized water were mixed to obtain a core layer initiator solution; A2: Add 0.3g sodium bicarbonate and 20g deionized water to a reaction flask and mix. Control the temperature at 50℃, add 20% of the core layer pre-emulsion and 25% of the core layer initiator solution, and keep the reaction at this temperature until the system emits a bluish light. Add the remaining core layer pre-emulsion and the remaining core layer initiator solution, and continue to keep the reaction at this temperature for 2.5h. Raise the temperature to 80℃, add the shell layer pre-emulsion and the shell layer initiator solution, and keep the reaction at this temperature for 4.5h. Control the temperature at 35℃, add ammonia water to adjust the pH to 8, and pass the mixture through a 200-mesh sieve to obtain a polyacrylate / styrene-butadiene rubber core-shell emulsion.

[0036] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the polyacrylate / styrene-butadiene rubber core-shell emulsion added in Example 1 is replaced with an equal amount of polyacrylate / styrene-butadiene rubber core-shell emulsion prepared in Comparative Example 1. The other components and preparation methods are completely consistent with those of Example 1.

[0037] Comparative Example 2: The preparation method of modified PVA fiber includes the following steps: B1: PVA fibers (8mm in length, 21μm in diameter, and 1.35GPa tensile strength) were cleaned with acetone, deionized water, and dried. They were then treated in an oxygen atmosphere at 100W for 5 minutes to obtain plasma-activated PVA fibers. B2: 1g of hexadecyltrimethylammonium bromide, 50mL of deionized water, and 150mL of anhydrous ethanol were added to a reaction flask for dispersion. 2mL of 28wt% ammonia water was added for dispersion, followed by 10g of plasma-activated PVA fiber and 3.5mL of tetraethyl orthosilicate. The reaction was carried out at 45℃ with stirring for 18h. The filtered solid was mixed with 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution to obtain a mixture. The solid was immersed in the mixture and refluxed for 8h. After washing and drying, mesoporous silica-modified PVA fiber was obtained. B3: Mix 1.5g sodium alginate, 100mL deionized water, and 0.2g lithium silicate, add 10g mesoporous silica-modified PVA fiber, control the temperature at 45℃ and keep it warm for 0.5h, filter, take the solid and immerse it in 50mL 1wt% calcium chloride solution, control the temperature at 25℃ and treat for 20min, wash and dry to obtain modified PVA fiber.

[0038] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the modified PVA fiber added in Example 1 is replaced by an equal amount of the modified PVA fiber prepared in Comparative Example 2, and the other components and preparation methods are completely consistent with those of Example 1.

[0039] Comparative Example 3: The preparation method of modified PVA fiber includes the following steps: B1: PVA fibers (8mm in length, 21μm in diameter, and 1.35GPa tensile strength) were cleaned with acetone, deionized water, and dried. They were then treated in an oxygen atmosphere at 100W for 5 minutes to obtain plasma-activated PVA fibers. 150 mL of anhydrous ethanol, 30 mL of deionized water, and 3 mL of 28 wt% ammonia were added to a reaction flask and dispersed. The temperature was controlled at 30 °C. 10 g of plasma-activated PVA fiber was added, along with 3-6 mL of tetraethyl orthosilicate. The temperature was controlled at 30-40 °C, and the mixture was stirred for 6-12 h. The mixture was then filtered, washed, and dried to obtain silica-modified PVA fiber. B2: Mix 1.5g sodium alginate, 100mL deionized water, and 0.2g lithium silicate, add 10g silica-modified PVA fiber, control the temperature at 45℃ and keep it warm for 0.5h, filter, take the solid and immerse it in 50mL 1wt% calcium chloride solution, control the temperature at 25℃ and treat for 20min, wash and dry to obtain modified PVA fiber.

[0040] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the modified PVA fiber added in Example 1 is replaced by an equal amount of the modified PVA fiber prepared in Comparative Example 3, and the other components and preparation methods are completely consistent with those of Example 1.

[0041] The preparation method of the modified PVA fiber in Comparative Example 4 includes the following steps: B1: PVA fibers (8mm in length, 21μm in diameter, and 1.35GPa tensile strength) were cleaned with acetone, deionized water, and dried. They were then treated in an oxygen atmosphere at 100W for 5 minutes to obtain plasma-activated PVA fibers. 150 mL of anhydrous ethanol, 30 mL of deionized water, and 3 mL of 28 wt% ammonia were added to a reaction flask and dispersed. The temperature was controlled at 30 °C. 10 g of plasma-activated PVA fiber was added, along with 3-6 mL of tetraethyl orthosilicate. The temperature was controlled at 30-40 °C, and the mixture was stirred for 6-12 h. The mixture was then filtered, washed, and dried to obtain silica-modified PVA fiber. B2: 1g of hexadecyltrimethylammonium bromide, 50mL of deionized water, and 150mL of anhydrous ethanol were added to a reaction flask for dispersion. 2mL of 28wt% ammonia water was added for dispersion, followed by 10g of silica-modified PVA fiber and 3.5mL of tetraethyl orthosilicate. The reaction was carried out at 45℃ with stirring for 18h. The filtered solid was mixed with 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution to obtain a mixture. The solid was immersed in the mixture and refluxed for 8h. After washing and drying, the modified PVA fiber was obtained.

[0042] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the modified PVA fiber added in Example 1 is replaced by an equal amount of the modified PVA fiber prepared in Comparative Example 4, and the other components and preparation methods are completely consistent with those of Example 1.

[0043] Comparative Example 5: The preparation method of modified nano-montmorillonite includes the following steps: C1: Add 10g of montmorillonite and 150mL of deionized water to a reaction flask and mix. Control the temperature at 55℃ and keep the reaction at this temperature for 1.5h. Add 0.7g of sodium carbonate, keep the reaction at this temperature and stir for 4.5h. Centrifuge, wash and dry to obtain sodium-based montmorillonite. C2: Add 10g of sodium montmorillonite and 150mL of deionized water to the reactor, and ultrasonically exfoliate at 400W for 1h while controlling the temperature at 50℃. Add 2g of hexadecyltrimethylammonium bromide and 30mL of anhydrous ethanol to the reactor, add hydrochloric acid to adjust the pH to 5, control the temperature at 60℃, and keep the reaction at this temperature for 4.5h. Wash and dry to obtain organically modified montmorillonite. C3: Under a nitrogen atmosphere, 10g of organically modified montmorillonite, 150mL of anhydrous ethanol, and 0.3g of azobisisobutyronitrile were added to a reaction flask and mixed. Then, 8.5g of methyl methacrylate, 5g of butyl acrylate, 2g of acrylic acid, and 1g of vinyltriethoxysilane were added. The temperature was controlled at 65℃ and the reaction was maintained for 7.5h. After centrifugation, washing, and drying, polymer-modified montmorillonite was obtained. C4: 10g of polymer-modified montmorillonite, 2g of hexadecyltrimethylammonium bromide, 120mL of anhydrous ethanol, and 30mL of deionized water were added to a reaction vessel and mixed. Ammonia was added to adjust the pH to 11. 5mL of tetraethyl orthosilicate was added, and the temperature was controlled at 45℃ for 9h. 1g of KH550 was added, and the reaction was maintained for 4.5h. The solid was obtained by centrifugation and washing. 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution were mixed to prepare a solution. The solid was immersed in the mixture and refluxed for 6h. After washing and drying, modified nano-montmorillonite was obtained.

[0044] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the modified nano-montmorillonite added in Example 1 is replaced with the modified nano-montmorillonite prepared in Comparative Example 5. The other components and preparation methods are completely the same as those of Example 1.

[0045] Comparative Example 6: The preparation method of modified nano-montmorillonite includes the following steps: C1: Add 10g of montmorillonite and 150mL of deionized water to a reaction flask and mix. Control the temperature at 55℃ and keep the reaction at this temperature for 1.5h. Add 0.7g of sodium carbonate, keep the reaction at this temperature and stir for 4.5h. Centrifuge, wash and dry to obtain sodium-based montmorillonite. C2: Add 10g of sodium montmorillonite and 150mL of deionized water to a reaction vessel, and ultrasonically exfoliate at 400W for 1h while controlling the temperature at 50℃. Add 2g of hexadecyltrimethylammonium bromide, 0.7g of KH570, 0.6g of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, and 30mL of anhydrous ethanol to the reaction vessel. Adjust the pH to 5 with hydrochloric acid, control the temperature at 60℃, and keep the reaction at this temperature for 4.5h. Wash and dry to obtain organically modified montmorillonite. C3: Under a nitrogen atmosphere, 10g of organically modified montmorillonite, 150mL of anhydrous ethanol, and 0.3g of azobisisobutyronitrile were added to a reaction flask and mixed. Then, 8.5g of methyl methacrylate, 5g of butyl acrylate, 2g of acrylic acid, and 1g of vinyltriethoxysilane were added. The temperature was controlled at 65℃ and the reaction was maintained for 7.5h. After centrifugation, washing, and drying, modified nano-montmorillonite was obtained.

[0046] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the modified nano-montmorillonite added in Example 1 is replaced with the modified nano-montmorillonite prepared in Comparative Example 6. The other components and preparation methods are completely the same as those of Example 1.

[0047] The preparation method of the modified nano-montmorillonite in Comparative Example 7 includes the following steps: C1: Add 10g of montmorillonite and 150mL of deionized water to a reaction flask and mix. Control the temperature at 55℃ and keep the reaction at this temperature for 1.5h. Add 0.7g of sodium carbonate, keep the reaction at this temperature and stir for 4.5h. Centrifuge, wash and dry to obtain sodium-based montmorillonite. C2: Add 10g of sodium montmorillonite and 150mL of deionized water to a reaction vessel, and ultrasonically exfoliate at 400W for 1h while controlling the temperature at 50℃. Add 2g of hexadecyltrimethylammonium bromide, 0.7g of KH570, 0.6g of bis-[γ-(triethoxysilyl)propyl]tetrasulfide, and 30mL of anhydrous ethanol to the reaction vessel. Adjust the pH to 5 with hydrochloric acid, control the temperature at 60℃, and keep the reaction at this temperature for 4.5h. Wash and dry to obtain organically modified montmorillonite. C3: 10g of organically modified montmorillonite, 2g of hexadecyltrimethylammonium bromide, 120mL of anhydrous ethanol, and 30mL of deionized water were added to a reaction vessel and mixed. Ammonia was added to adjust the pH to 11. 5mL of tetraethyl orthosilicate was added, and the temperature was controlled at 45℃ and the reaction was maintained for 9h. 1g of KH550 was added, and the reaction was maintained for 4.5h. The solid was obtained by centrifugation and washing. 100mL of anhydrous ethanol and 1mL of 37wt% hydrochloric acid aqueous solution were mixed to prepare a mixture. The solid was immersed in the mixture and refluxed for 6h. After washing and drying, modified nano-montmorillonite was obtained.

[0048] The preparation method of polymer-modified asphalt cement mortar is the same as that of Example 1, except that the modified nano-montmorillonite added in Example 1 is replaced with the modified nano-montmorillonite prepared in Comparative Example 7. The other components and preparation methods are completely the same as those of Example 1.

[0049] Comparative Example 8: Preparation method of polymer-modified asphalt cement mortar. Compared with Example 1, only the polyacrylate / styrene-butadiene rubber core-shell emulsion added in Example 1 was deleted, the modified PVA fiber added in Example 1 was replaced with an equal amount of PVA fiber, and the modified nano-montmorillonite added in Example 1 was replaced with an equal amount of nano-montmorillonite. The remaining components and preparation methods were completely consistent with Example 1.

[0050] Performance testing The polymer-modified asphalt cement mortar prepared in Examples 1-3 and Comparative Examples 1-8 was injected into the mold, leveled with a screed, and the surface of the specimen was covered with a film. The specimen was then moved into a standard curing room for curing. After 1 day, the specimen was demolded and continued to be cured in the standard curing room for 7 days. Then it was moved into a curing room with a temperature of 20±2℃ and a humidity of 60%±5% for curing. (1) Mechanical properties Flexural and compressive strength: According to GB / T 17671-2021 "Test Method for Strength of Cement Mortar", the force-deflection curve was tested and the flexural strength was calculated using a SANS universal testing machine. The support span was 100 mm, and the uniform loading rate was 0.5 mm / min until fracture. The two sides of the specimen during molding were subjected to compression tests using the broken prism. The loading rate of the press was 2400 N / s. The flexural and compressive strength of the specimens cured for 28 days were tested. The test results are shown in Table 1. Splitting tensile strength: Tested according to GB / T 50081 "Standard for Test Methods of Performance of Ordinary Concrete", and the test results are shown in Table 1; Table 1: Statistical Table of Mechanical Property Test Data for Examples 1-3 and Comparative Examples 1-8

[0051] As shown in Table 1, the polymer-modified asphalt cement mortar prepared in this application has excellent mechanical properties.

[0052] (2) Durability Impermeability: Tested according to GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", the test results are shown in Table 2; Freeze-thaw durability: According to GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete", the mass loss and relative dynamic modulus of elasticity were tested after 300 freeze-thaw cycles. The test results are shown in Table 2. Bleeding rate: The test was conducted according to DL / T 5126-2001 "Test Procedure for Polymer Modified Cement Mortar", and the test results are shown in Table 2. Drying shrinkage rate: The drying shrinkage rate after 120 days was tested according to GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". The test results are shown in Table 3. High and low temperature performance: According to JTG E30-2015 "Test Procedures for Cement and Cement Concrete in Highway Engineering", the low temperature flexural strength at -20℃ and the resistance to rutting creep at 60℃ / 24h were tested. The test results are shown in Table 3. UV aging resistance: According to GB / T 16422.3 "Plastic Xenon Lamp Aging" and JTJ052-2000 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", the material was subjected to UV aging for 500 hours, and then the compressive strength of the material was tested. The compressive strength retention rate was calculated. The test results are shown in Table 3. UV aging resistance: According to GB / T 16422.3 "Plastic Xenon Lamp Aging" and JTJ052-2000 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", the material was subjected to UV aging for 500 hours, and then the compressive strength of the material was tested. The compressive strength retention rate was calculated. The test results are shown in Table 3. Table 2: Statistical table of durability performance test data for Examples 1-3 and Comparative Examples 1-8 (1)

[0053] Table 3: Statistical table of durability performance test data for Examples 1-3 and Comparative Examples 1-8 (2)

[0054] As shown in Table 2, the polymer-modified asphalt cement mortar prepared in this application has excellent durability.

[0055] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A method for preparing polymer-modified asphalt cement mortar, characterized in that, Includes the following steps: Cement, fine aggregate, and modified nano-montmorillonite are blended to obtain a dry mix; The composite retarder, water-reducing agent, water, and polyacrylate / styrene-butadiene rubber core-shell emulsion were blended to obtain the liquid phase component; The dry mixture, liquid phase component, and cationic emulsified asphalt are blended together, and a defoamer is added for blending. Modified PVA fiber is added for blending, and an air-entraining agent is added for blending to obtain polymer-modified asphalt cement mortar. The modified nano-montmorillonite is obtained by organic treatment with hexadecyltrimethylammonium bromide, KH570, and bis-[γ-(triethoxysilyl)propyl]tetrasulfide as intercalating agents, followed by polymer interface modification and surface mesoporous silica functionalization. The preparation method of the modified PVA fiber includes the following steps: A1: Anhydrous ethanol, deionized water, and 25-28 wt% ammonia water are added to a reaction flask and dispersed. The temperature is controlled at 30-35℃. Plasma-activated PVA fibers are added, and tetraethyl orthosilicate is added. The temperature is controlled at 30-40℃ and the reaction is stirred for 6-12 hours. The mixture is then filtered, washed, and dried to obtain silica-modified PVA fibers. A2: Hexadecyltrimethylammonium bromide, deionized water, and anhydrous ethanol were added to a reaction flask for dispersion. 25-28 wt% ammonia water was added for dispersion. Silica-modified PVA fibers were added, along with tetraethyl orthosilicate. The reaction was carried out at a temperature of 40-50℃ with stirring for 12-24 hours. The mixture was filtered, and the solid was immersed in an ethanol mixture containing hydrochloric acid. The mixture was refluxed for 6-12 hours for extraction. After washing and drying, mesoporous silica-modified PVA fibers were obtained. A3: Sodium alginate, deionized water, and lithium silicate are mixed together, and mesoporous silica-modified PVA fibers are added. The temperature is controlled at 40-50℃ and kept warm for 0.5-1h. After filtration, the solid is immersed in calcium chloride solution and the temperature is controlled at 20-25℃ for 10-30min. After washing and drying, modified PVA fibers are obtained.

2. The method for preparing polymer-modified asphalt cement mortar according to claim 1, characterized in that, The addition ratio of anhydrous ethanol, deionized water, 25-28wt% ammonia, plasma-activated PVA fiber, and tetraethyl orthosilicate in A1 is 150-200mL: 20-40mL: 2-4mL: 10g: 3-6mL. A2 contains ethanol and hydrochloric acid mixtures composed of 100-150 mL of anhydrous ethanol and 1-2 mL of 37 wt% hydrochloric acid aqueous solution; The addition ratio of hexadecyltrimethylammonium bromide, deionized water, anhydrous ethanol, 25-28 wt% ammonia, silica-modified PVA fiber, tetraethyl orthosilicate, and ethanol containing hydrochloric acid in A2 is 0.5-1.5 g: 50-80 mL: 100-150 mL: 1-3 mL: 10 g: 2-5 mL: 100-150 mL; The calcium chloride solution in A3 is a 0.5-1 wt% aqueous solution of calcium chloride; The addition ratio of sodium alginate, deionized water, lithium silicate, mesoporous silica-modified PVA fiber, and calcium chloride solution in A3 is 1-2g: 50-100mL: 0.1-0.3g: 10g: 50-100mL.

3. The method for preparing polymer-modified asphalt cement mortar according to claim 1, characterized in that, The preparation method of the modified nano-montmorillonite includes the following steps: B1: Sodium-based montmorillonite and deionized water were added to a reaction vessel and ultrasonically treated. The temperature was controlled at 45-55℃. Cetyltrimethylammonium bromide, KH570, bis-[γ-(triethoxysilyl)propyl]tetrasulfide and anhydrous ethanol were mixed and added to the reaction vessel. Hydrochloric acid was added to adjust the pH to 4-5. The temperature was controlled at 55-65℃ and the reaction was kept at this temperature for 3-6 hours. After washing and drying, organic modified montmorillonite was obtained. B2: Under a nitrogen atmosphere, organic modified montmorillonite, anhydrous ethanol, and azobisisobutyronitrile were added to a reaction flask and mixed together. Methyl methacrylate, butyl acrylate, acrylic acid, and vinyltriethoxysilane were added. The temperature was controlled at 60-70℃ and the reaction was kept at this temperature for 6-9 hours. After centrifugation, washing, and drying, polymer-modified montmorillonite was obtained. B3: Polymer-modified montmorillonite, hexadecyltrimethylammonium bromide, anhydrous ethanol, and deionized water were added to a reaction vessel and mixed. Ammonia was added to adjust the pH to 10-11. Tetraethyl orthosilicate was added, and the temperature was controlled at 40-50℃ for 6-12 hours. KH550 was added, and the reaction was maintained for 3-6 hours. After centrifugation and washing, the mixture was added to an ethanol mixture containing hydrochloric acid and refluxed for 4-6 hours. After washing and drying, modified nano-montmorillonite was obtained.

4. The method for preparing polymer-modified asphalt cement mortar according to claim 3, characterized in that, The preparation method of sodium-based montmorillonite includes the following steps: adding montmorillonite and deionized water into a reaction flask for mixing, controlling the temperature at 50-60℃ and keeping the reaction at this temperature for 1-2 hours, adding sodium carbonate, keeping the reaction at this temperature and stirring for 3-6 hours, centrifuging, washing and drying to obtain sodium-based montmorillonite. The addition ratio of montmorillonite, deionized water, and sodium carbonate is 10g: 100-200mL: 0.5-1g.

5. The method for preparing polymer-modified asphalt cement mortar according to claim 3, characterized in that, The addition ratio of sodium montmorillonite, deionized water, hexadecyltrimethylammonium bromide, KH570, bis-[γ-(triethoxysilyl)propyl]tetrasulfide, and anhydrous ethanol in B1 is 10g: 100-200mL: 1.5-2.5g: 0.5-1g: 0.4-0.8g: 20-40mL; The addition ratio of organic modified montmorillonite, anhydrous ethanol, azobisisobutyronitrile, methyl methacrylate, butyl acrylate, acrylic acid, and vinyltriethoxysilane in B2 is 10g: 100-200mL: 0.2-0.4g: 7-10g: 4-6g: 1-3g: 0.8-1.2g; B3 contains an ethanol mixture with hydrochloric acid, which consists of 100-150 mL of anhydrous ethanol and 1-2 mL of 37 wt% hydrochloric acid aqueous solution. The addition ratio of polymer-modified montmorillonite, hexadecyltrimethylammonium bromide, anhydrous ethanol, deionized water, tetraethyl orthosilicate, and KH550 in B3 is 10g: 1.5-2.5g: 80-160mL: 20-40mL: 4-6mL: 0.8-1.2g.

6. The method for preparing polymer-modified asphalt cement mortar according to claim 1, characterized in that, The preparation method of the polyacrylate / styrene-butadiene rubber core-shell emulsion includes the following steps: C1: Butadiene, styrene, and methacrylic acid are added to a reaction flask and mixed together. Allyloxynonylphenol polyoxyethylene ether ammonium sulfate, sodium dodecylbenzene sulfonate, OP-10, and deionized water are added and mixed together to obtain a core layer pre-emulsion. Methyl methacrylate, butyl acrylate, glycidyl methacrylate, N-hydroxymethylacrylamide, and acrylic acid were added to a reaction flask and dispersed. Allyloxynonylphenol polyoxyethylene ether ammonium sulfate and deionized water were added and mixed to obtain a shell pre-emulsion. Potassium persulfate and deionized water were mixed to obtain a core layer initiator solution; Potassium persulfate and deionized water were mixed to obtain a core layer initiator solution; C2: Add sodium bicarbonate and deionized water to the reaction flask and mix. Control the temperature at 50-55℃. Add part of the core layer pre-emulsion and part of the core layer initiator solution. Keep the reaction at this temperature until the system emits a bluish light. Add the remaining core layer pre-emulsion and the remaining core layer initiator solution. Continue to keep the reaction at this temperature for 2-3 hours. Raise the temperature to 75-80℃, add the shell layer pre-emulsion and the shell layer initiator solution. Keep the reaction at this temperature for 3-6 hours. Control the temperature at 30-40℃. Add ammonia water to adjust the pH to 7.5-8. Sieve the mixture to obtain a polyacrylate / styrene-butadiene rubber core-shell emulsion.

7. The method for preparing polymer-modified asphalt cement mortar according to claim 6, characterized in that, The core layer preemulsion comprises the following raw materials in parts by weight: 45-60 parts by weight of butadiene, 25-35 parts by weight of styrene, 2-5 parts by weight of methacrylic acid, 1.2-2.4 parts by weight of allyloxynonylphenol polyoxyethylene ether ammonium sulfate, 0.5-1.5 parts by weight of sodium dodecylbenzenesulfonate, 0.5-1.5 parts by weight of OP-10, and 40-60 parts by weight of deionized water; The shell preemulsion comprises the following raw materials in parts by weight: 25-35 parts by weight of methyl methacrylate, 15-20 parts by weight of butyl acrylate, 8-12 parts by weight of glycidyl methacrylate, 3-6 parts by weight of N-hydroxymethylacrylamide, 2-5 parts by weight of acrylic acid, 0.8-1.6 parts by weight of allyloxynonylphenol polyoxyethylene ether ammonium sulfate, and 30-45 parts by weight of deionized water; The core layer initiator solution comprises the following raw materials in parts by weight: 0.2-0.4 parts by weight of potassium persulfate and 7.5-11.25 parts by weight of deionized water; The shell initiator solution comprises the following raw materials in parts by weight: 0.2-0.4 parts by weight of potassium persulfate and 7.5-11.25 parts by weight of deionized water; The mass ratio of partial core layer preemulsion to remaining core layer preemulsion is 1:4; The mass ratio of a portion of the core layer initiator solution to the remaining core layer initiator is 1:3; The mass ratio of sodium bicarbonate, deionized water, and shell initiator solution in C2 is 0.2-0.5: 15-22.5: 7.7-11.

65.

8. The method for preparing polymer-modified asphalt cement mortar according to claim 1, characterized in that, The polymer-modified asphalt cement mortar comprises the following raw materials in parts by weight: 100 parts by weight of cement, 150-200 parts by weight of fine aggregate, 0.5-2 parts by weight of modified nano-montmorillonite, 0.2-0.5 parts by weight of composite retarder, 0.5-1 parts by weight of water-reducing agent, 10-20 parts by weight of polyacrylate / styrene-butadiene rubber core-shell emulsion, and 30-50 parts by weight of cationic emulsified asphalt blend, with the addition of 0.1-0.3 parts by weight of defoamer, 0.5-1.5 parts by weight of modified PVA fiber, and 0.01-0.05 parts by weight of air-entraining agent; the water-cement ratio of the polymer-modified asphalt cement mortar is 0.38-0.

45.

9. The method for preparing polymer-modified asphalt cement mortar according to claim 1, characterized in that, The cement is silicate cement; The fine aggregate is river sand with a particle size of 0.16-4.75 mm and a fineness modulus of 1.8-2.6; The composite retarder is composed of citric acid and aluminum sulfate in a mass ratio of 1:1; The water-reducing agent is a polycarboxylate water-reducing agent; The defoamer is an organosilicone defoamer; The air-entraining agent is a rosin-based air-entraining agent.

10. Polymer-modified bitumen cement mortar, characterized in that, It is prepared by the method described in any one of claims 1-9.